ON DISABILITY, SOCIETY AND TECHNOLOGY: AN INFORMAL CONVERSATION FROM SOUTH INDIA (International Journal of Engineering Sciences & Management Research, 2017)
This article reproduces partially the lecture I delivered at the Albertian Institute of Science and Technology (AISAT), Kochi, Kerala, India, on September 3, 2016. The main focus is the relationship between disability, society and Technology; it also stresses the essential role played by Christianity not only in what regards the social integration of the disabled and the development of Assistive Technology, but also in the development of Science and Technology in general.